Molecular and serological evidence of Crimean-Congo hemorrhagic fever orthonairovirus prevalence in livestock and ticks in Cameroon - Simo Tchetgna, Huguette; Yousseu, Francine S.; Cosset, François-Loïc; de Freitas, Natalia Bezerra; Kamgang, Basile; McCall, Philip J.; Ndip, Roland Ndip; Legros, Vincent; Wondji, Charles S. (Frontiers in Cellular and Infection Microbiology, 2023)
Despite a high fatality rate in humans, little is known about the occurrence of Crimean-Congo hemorrhagic fever virus (CCHFV) in Cameroon. Hence, this pioneer study was started with the aim of determining the prevalence of CCHFV in domestic ruminants and its potential vector ticks in Cameroon. A cross-sectional study was carried out in two livestock markets of Yaoundé to collect blood and ticks on cattle, sheep, and goats. CCHFV-specific antibodies were detected in the plasma using a commercial ELISA assay and confirmed using a modified seroneutralization test. Ticks were screened for the presence of orthonairoviruses by amplification of a fragment of the L segment using RT-PCR. Phylogeny was used to infer the genetic evolution of the virus. Overall, 756 plasma samples were collected from 441 cattle, 168 goats, and 147 sheep. The seroprevalence of CCHFV was 61.77% for all animals, with the highest rate found in cattle (433/441, 98.18%) followed by sheep (23/147, 15.65%), and goats (11/168, 6.55%), (p-value < 0.0001). The highest seroprevalence rate was found in cattle from the Far North region (100%). Overall, 1500 ticks of the Rhipicephalus (773/1500, 51.53%), Amblyomma (341/1500, 22.73%), and Hyalomma (386/1500, 25.73%) genera were screened. CCHFV was identified in one Hyalomma truncatum pool collected on cattle. Phylogenetic analysis of the L segment classified this CCHFV strain within the African genotype III. These results call for increased epidemiological studies on CCHFV, especially among at-risk human and animal populations in high-risk areas of the country.